Tingkat Kepatuhan Syariah Bank Pembiayaan Rakyat Syariah Berbasis Maqashid Syariah - Shabri, Husni; Amalia, Euis (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2022)
Knowledge of shariah compliance in the sharia banking industry is still low. Shariah compliance is a special uniqueness that exists in sharia banking. The correct knowledge of shariah compliance has an important urgency in the operations of Islamic banks. The purpose of this study was to determine the level of sharia compliance of Islamic Rural Banks in Indonesia. The research method uses a quantitative descriptive approach. The data source of this research is secondary data. The data collection technique uses documentation in the form of annual reports of all Sharia Rural Banks (BPRS) which are the combined financial statements of BPRS in the Sharia Banking Statistics Report for September 2021 Otoritas Jasa Keuangan (OJK) with a total of 165 BPRS. The results show that the level of sharia compliance of Islamic Rural Banks (BPRS) as measured by the Maqashid Shariah Index (MSI) for a period of 10 years is still very low with an average index value of 0.32319 or 32.319%. Research findings reveal that the allocation of funds to aspects of education, research and training as well as the ratio of zakat to income is very relatively low, even information related to zakat payments until 2018 is non-existent or zero. The results of this study can be used as input for the management of Islamic Rural Banks (BPRS) special attention to the dimensions of which the index value is still very low